Unveiling EFL students’ views on gamified learning experience: A survey study - Armanda, Muhamad Laudy; Priyana, Joko (Englisia Journal, 2025)
Gamification has gained power in education for its potential to boost student motivation through engaging, game-like experiences. However, the specific dimensions driving its effectiveness in language learning remain underexplored. This study investigates English as a Foreign Language (EFL) students’ perceptions of gamified learning tools (e.g., Classcraft, Kahoot! Quizizz, Duolingo) in enhancing their English acquisition. A cross-sectional survey design was employed, utilizing the GAMEFULQUEST online questionnaire to capture immediate responses from 155 EFL students at a state university in Central Java, Indonesia. Participants, selected via purposive sampling, had experience with gamified learning platforms inside and outside the classroom. Findings revealed high satisfaction across all seven dimensions of the gamified experience, with no significant variations by gender or age. These results highlight the universal appeal of gamification in EFL contexts and provide a foundation for future research.